Association of physical activity and sedentary time with scoliosis screening positive in Chinese primary and secondary school students: a cohort study in Shanghai - Chu, Liting; Yang, Dongling; Zhang, Fengyun; Qi, Wenjuan; Huang, Yuting; Yang, Yanting; Qu, Shuangxiao; Huang, Shenglei; Zheng, Keyang; Luo, Chunyan (Frontiers in Public Health, 2025)
BackgroundThe relationship between physical activity (PA), sedentary time (ST), and scoliosis screening positive (SSP) among Chinese students has not been extensively studied. This study aims to explore this association using data from the Shanghai Municipal Dynamic Cohort of Student Common Diseases (SMDCSCD).MethodsWe conducted a repeated measures study over three waves (2021, 2022, and 2023). SSP was determined through physical examinations, while PA and ST data were collected via questionnaires. Sufficient moderate to vigorous PA (MVPA) was defined as more than 60 min per day, and excessive ST was classified as sitting for 4.5 h or more daily.ResultsThe study included 6,829 students with 19,673 observations. The prevalence of SSP ranged from 0.11% in Grade 1 to 2.77% in Grade 8 (P-trend < 0.001). Significant differences in ST (minutes/day) were found between the SSP and scoliosis screening negative (SSN) groups in the first 2 years (p = 0.026 and p = 0.023, respectively), but no significant differences were observed in total PA levels (MET-min/week) (p > 0.05). In a multivariable-adjusted model, ST of 4.5 h or more per day was positively associated with SSP (OR = 2.405, 95% CI: 1.323 to 4.374). No significant association was found between PA and SSP (p > 0.05).ConclusionThe prevalence of positive scoliosis screening increased with grade level. Longer sedentary time was significantly associated with a higher likelihood of positive scoliosis screening, while no significant association was found between physical activity levels and scoliosis screening outcomes. These findings suggest that reducing sedentary time may be important for scoliosis prevention in students, highlighting the need for targeted interventions to promote healthier daily habits.